The Structure and Dimensional Design of a Reconfigurable PKM. (10th June 2013) - Tang, Xiaoqiang; Sun, Dengfeng; Shao, Zhufeng
Parallel Kinematic Machines (PKMs) have many advantages and have been widely used in the machine industry. Benefitting from its modular structure, a PKM is more reconfigurable than traditional serial machines. In this paper, a new type of driving strut module and innovative joints are designed for the Reconfigurable Parallel Kinematic Machine (RPKM). The new driving strut module can be changed from linear drive mode to telescopic drive mode easily, and the new spherical joint and universal joint are designed to achieve a large rotation angle. The inverse kinematics problems in relation to the 6-DOF RPKM are analysed, and the Workspace Volume Index (WVI) and the Global ConditionIndex (GCI) are adopted to design the RPKM. According to the WVI and GCI analysis of the selected parameters for two types of 6-DOF PKM, the dimensional parameters of the RPKM are designed. In the end, the new type of RPKM prototype is built, with which a wax pattern is machined.